Financial Planning (Fiping) Project: Educational Website in Improving Student Understanding Through Literacy Finance and Financial Planning Independently - Adawiyah, Robiah Al; Ritmaya, Chitra Laksmi; Soebijanto, Ali (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
Knowledge and understanding of financial literacy and planning still need to be in the low category, which, in this case, impacts unwise financial management. This statement is supported by data from the Central Statistics Agency (BPS) for the September 2022 period, there was an increase in the number of poor people by 9.57%. Improving financial management capabilities through increasing understanding of financial literacy and financial planning can be started by the younger generation, namely students. These improvement efforts can be adapted to the current era of digitalization, namely with a digital educational website platform. This research aims to realize alternative solutions based on the results of research that has been done in the form of a financial planning project website equipped with supporting features. As well as outlining the obstacles and completion of the realization of the financial planning project website. Data collection methods with descriptive research methods through questionnaires, interviews, and observation. Research results on students show that there are still problems in understanding financial literacy and financial planning independently, so researchers offer an alternative solution called the financial planning project. The research implications explain that the financial planning project media benefits students by increasing their financial literacy and independent financial planning and their interest in saving, doing business, and investing at a young age. In addition, it can minimize the financial problems that students have faced.